MODEL PEMBELAJARAN TERPADU DI SEKOLAH DASAR - Uum Murfiah (Universitas Syiah Kuala, 2022)
Integrated learning is a learning model that has meaningful benefits for learners in everyday life. Integrated learning implemented in elementary schools will color a comprehensive process and learning outcomes. For that purpose, the preparation, planning, execution and assessment is a unified learning system. The role of teachers in the success of integrated learning in primary schools requires careful planning, the execution of the learners' fun, and a comprehensive assessment of the attitudes, knowledge and skills learned by learners. The integrated learning model uses an inter-subject approach. This model is an approach of integration between topics by combining concepts in math, science, language and art and social knowledge. This model is implemented by combining the subjects (interdisciplinary), setting priority of subject matter, skills, concepts and attitudes that are interrelated in some subjects. To create a theme, the teacher must first select the concept of several subjects, then be linked in a theme to cover several subjects, in a themed learning package.